Analisis Kinerja Keuangan Pengelolaan Dana Desa Berdasarkan Rasio Efektivitas dan Rasio Efisiensi Pada Desa Padamulya Kecamatan Majalaya Kabupaten Bandung - Gunawan; Fauziah, Lilis Nur (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to evaluate the effectiveness and efficiency of financial management in Padamulya Village, Majalaya District, Bandung Regency, with a focus on the ADD (APBD) for the years 2022 and 2023. Given that the data analyzed consists of numerical figures from financial reports, this study employs a qualitative approach with data collection methods including interviews and documentation techniques. Data analysis is conducted descriptively using the effectiveness and efficiency ratio calculations. The findings indicate that the financial management by the Padamulya Village Government has been well-executed. The effectiveness ratio of village funds for 2022–2023 is categorized as effective, signifying that the village has successfully met its financial targets. However, variations in budget effectiveness were observed, primarily due to certain allocations disbursed at the end of the year that were not immediately realized and were only completed in the following year. Nevertheless, various planned programs were successfully implemented as expected. From an efficiency perspective, the village's budget management during this period was carried out optimally. The Padamulya Village Government considers an activity effective if it is implemented according to the predetermined plan. Overall, the village's financial management has demonstrated a positive performance in supporting local development and community welfare.